(untitled) (REMUNOM, 2025)
Supplementation of cattle on pasture is a practice widely adopted by cattle breeders seeking to increase productivity in beef cattle. Among the available strategies, the use of low-consumption protein products stands out as a technological alternative capable of intensifying production systems. This study aims to evaluate the efficiency of the use of low-intake proteins in the nutrition of beef cattle, considering their impacts on productive performance, especially on weight gain, and their viability as a supplementation strategy in pasture breeding systems. The study involved 60 non-castrated male cattle, aged between 12 and 15 months, of the Nellore breeds, distributed in two groups: supplementation with B25-4 (30 animals), standard farm diet (30 animals). The trial period lasted 120 days. The animals supplemented with B25-4 showed an average daily weight gain of 0.725 kg, while the control group obtained a gain of 0.475 kg. The 52.63% increase in the weight gain of the supplemented animals may be related to the greater nutrient intake provided by the protein. Thus, the adoption of advanced formulation proteins, such as B25-4, can be an effective strategy to increase productivity.